Solid state fermentation process with Aspergillus kawachii enhances the cancer-suppressive potential of silkworm larva in hepatocellular carcinoma cells - Hyun-Dong Cho; Hye-Ji Min; Yeong-Seon Won; Hee-Young Ahn; Young-Su Cho; Kwon-Il Seo (BMC, 2019)
Abstract Background Mulberry silkworm larvae (Bombyx mori) are known as the oldest resource of food and traditional medicine. Although silkworm larvae have been reported to treat various chronic diseases, the effect of fermentation by microorganisms improving the biological activities of silkworm larvae was not reported. In the present study, fermented silkworm larvae was developed via solid-state fermentation with Aspergillus kawachii and investigated its anti-cancer activity in human hepatocellular carcinoma cells. Methods We investigated the anti-cancer effects of unfermented (SEE) and fermented silkworm larva ethanol extract (FSEE) on HepG2 human hepatocellular carcinoma cells as well as compared changes in free amino acid, fatty acid, and mineral contents. Anti-cancer activities were evaluated by SRB staining, cell cycle analysis, Annexin V staining, Hoechst staining, DNA fragmentation analysis and western blot analysis. Fatty acid, free amino acid and mineral contents of SEE and FSEE were determined by gas chromatography, amino acid analyzer and flame atomic absorption spectrophotometer, respectively. Results Compared with SEE, treatment with FSEE resulted in apoptotic cell death in HepG2 cells characterized by G0/G1 phase cell cycle arrest, DNA fragmentation, and formation of apoptotic bodies. Furthermore, FSEE significantly up-regulated pro-apoptotic as well as down-regulated anti-apoptotic proteins in HepG2 cells. However, an equivalent concentration of SEE did not induce cell cycle arrest or apoptosis in HepG2 cells. Moreover, fermentation process by Aspergillus kawachii resulted in enhancement of fatty acid contents in silkworm larvae, whereas amino acid and mineral contents were decreased. Conclusion Collectively, this study demonstrates that silkworm larvae solid state-fermented by Aspergillus kawachii strongly potentiates caspase-dependent and -independent apoptosis pathways in human hepatocellular carcinoma cells by regulating secondary metabolites.